2019
DOI: 10.1002/jgm.3107
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of CRISPR/Cas9 for therapeutic genome editing

Abstract: The clustered, regularly‐interspaced, short palindromic repeat (CRISPR)‐associated nuclease 9 (CRISPR/Cas9) is emerging as a promising genome‐editing tool for treating diseases in a precise way, and has been applied to a wide range of research in the areas of biology, genetics, and medicine. Delivery of therapeutic genome‐editing agents provides a promising platform for the treatment of genetic disorders. Although viral vectors are widely used to deliver CRISPR/Cas9 elements with high efficiency, they suffer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 159 publications
(297 reference statements)
0
69
0
1
Order By: Relevance
“…Non‐viral vectors with a better safety profile usually do not possess sufficient transfection efficiency. [ 7–12 ] The reported non‐viral vectors cover diverse materials such as lipid‐like materials, [ 13,14 ] cell exosomes, [ 15 ] polymers and their hybrids, [ 16–22 ] nucleic acid based materials, [ 23 ] and metal containing materials. [ 24–26 ] Nevertheless, in spite of extensive studies on functionalization of non‐viral vectors, the studies on the vectors for delivery of genome editing plasmids are relatively rare.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐viral vectors with a better safety profile usually do not possess sufficient transfection efficiency. [ 7–12 ] The reported non‐viral vectors cover diverse materials such as lipid‐like materials, [ 13,14 ] cell exosomes, [ 15 ] polymers and their hybrids, [ 16–22 ] nucleic acid based materials, [ 23 ] and metal containing materials. [ 24–26 ] Nevertheless, in spite of extensive studies on functionalization of non‐viral vectors, the studies on the vectors for delivery of genome editing plasmids are relatively rare.…”
Section: Methodsmentioning
confidence: 99%
“…To realize safe delivery of CRISPR‐Cas9 plasmids into targeted tumor cells with a high efficiency is still challenging. [ 10,11 ]…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been reported that the lipid nanoparticle-mediated delivery of Cas9 mRNA with AAVs encoding a sgRNA and a repair template to induce repair of a disease gene in adult animals showed successful genome editing and therapeutic effect [32]. Further efforts are necessary to develop the safe and effective delivery of the CRISPR/Cas9 system [180].…”
Section: Recent Progressmentioning
confidence: 99%
“…In addition to the previously described gene therapy approaches based on both gene supplementation and gene suppression strategies, recent advances on genome editing tools by CRISPR/Cas technology allow the correction of a specific mutation at a genomic level [18]. Due to the huge treatment possibilities of such revolutionary genome editing tools, the number of scientific publications in this area has considerably increased since 2014, and many clinical trials are underway, especially in cancer and pathological disorders of the blood and eye [19].…”
Section: Introductionmentioning
confidence: 99%